Effect of Supplementation of Phyto-pharmaceutical Product on the Health and Productivity of Crossbred Cows during Transition Period: Effect of Supplementation of Phyto-pharmaceutical Product on the Health.. - Sharma, Lakshit; Dang, Ajay Kumar; Sharma, Shikha; Singh, Tarun Pal (Indian Journal of Dairy Science, 2023)
The present study was conducted to investigate the efficacy of supplementation of phyto-pharmaceutical product on the immune status of cows during transition period. Twelve crossbred cows in their late gestation were selected and randomly divided into two groups as control group (CON) and supplemented group (SG). The cows in the CON were fed as per the NRC standards while SG were supplemented additionally with 20g of poly-herbal formulation containing Boswellia serrata (Burseraceae) and 20g of Berginia ciliata (Saxifragaceae) for 21 days prepartum to 7 days postpartum. Immune status viz., total leucocyte count (TLC), neutrophil percentage (%), lymphocyte percentage (%), neutrophil: lymphocyte ratio (N:L), in-vitro phagocytic activity (PA) of blood neutrophils, plasma cortisol level, interleukin-2 (IL-2) and interleukin-8 (IL-8) were estimated as well as effects were studied on milk for somatic cell count (SCC) and its constituents (fat, protein and lactose) too. Results showed that supplementation mixture significantly (P